A Probable Neoceratopsian Manus Track from the Nanushuk Formation (Albian, Northern Alaska) - Fiorillo, A. R.; Decker, P. L.; LePain, D. L.; Wartes, M.; McCarthy, P. J. (Journal of Iberian Geology, 2010)
We report a likely neoceratopsian manus track from an exposure of the Nanushuk Formation along the Colville River in northern Alaska. The track described here containts the impressions of five digits, arranged as an arc, which identify this specimen as a manus. Details of the impression suggest that it is neoceratopsian rather than ankylosaurian. The length of the chord of the arc of the track is approximately 25 cm, which is half the size of manus tracks found west of Denver, Colorado, USA attributed to the 10 m long Maastrichtian Triceratops. The Nanushuk Formation is a succession of complexly intertonguing marine and nonmarine strata interpreted as shelf, deltaic, strandplain, fluvial, and alluvial overbank deposits. Deposited in the foreland basin north f the Brooks Range, the rock unit is present throughout most of the northern foothills belt and subsurface of the central and western North Slope coastal plain. Fossil and radiometric data place outcrop within the Albian. If the identification of the track is correct, this is one of the earlies occurrences of neoceratopsians from North America. The occurrence of this track in Alaska substantiates the biogeographic model of faunal exchange between Asia and North America through a Cretaceous land bridge known as Beringia.